Real Time Qos in Wsn Based Network Coding and Reinforcement Learning - Sghaier, Amra; Medeb, Aref (Informatica, 2023)
In recent years, wireless sensor networks have witnessed tremendous advancements due to a reduction in development costs. This rapid growth of WSN gave rise to a variety of potential and emerging applications, such as real time application which are challenging because of their huge requirements. As the number of applications grows, the need for providing both reliable and real time QoS communication in a resource constrained WSN becomes one of the paramount issues. To overcome this problem, we address to use network coding (NC) in the one hand, which is a new area of research that can be applied in dierent environments and solve several shortcomings within a network. On the other hand, we focus on duty cycle, which is considered to be one of the most popular techniques for saving energy. Specially, we apply the duty cycle learning algorithm (DCLA) in order to nd the optimal duty cycle. In order to guarantee expected real time QoS and reliability, we propose NCDCLA (Network Coding based Duty Cycle Learning Algorithm). Through simulation in OPNET, our results show that our approach can achieve a good reliable performance.